HUBUNGAN EFIKASI DIRI DENGAN KEPATUHAN MELAKUKAN LATIHAN FISIK PADA PASIEN DIABETES MELLITUS TIPE 2 - Mia Widha Anindita; Noor Diani; Ifa Hafifah (Faculty of Medicine, Hasanuddin University., 2019)
Introduction: Diabetes mellitus is a chronic disease, and type 2 DM accounts for 90-95% of total diabetes. Adherence to implementation of physical exercise is very necessary for patients with DM. Self efficacy in diabetic patients can improve the adherence for medications and success to control the sugar levels.Methods: We aimed to analyze the correlation between self efficacy and adherence to physical exercises in type 2 diabetes patients. This is a descriptive cross-sectional study with purposive sampling method. In total, we recruit 60 respondents during December 2018. We used two types of questionnires: self efficacy and adherence to physical exercises to measure the variable of interest.Result: We found that there was a correlation between self efficacy and adherence to physical exercises in type 2 diabetic patients (p<0.001).Conclusion: Appropriate self efficacy could improve patients’ adherence to manage the advised physical examination.